{[2-Methyl-2-(phenoxymethyl)propane-1,3-diyl]bis(oxy)}dibenzene - Moussa, Ziad (International Union of Crystallography, 2014)
The title compound, C(23)H(24)O(3), was obtained in a one-step (60% yield) synthesis from 1,1,1-tris(hydroxymethyl)ethane. It features a tripodal ligand capable of complexing metal centres. One of the three conformations involving the methyl group, the central C—C bond and the phenoxy substituents is antiperiplanar while the two others are synclinal [the corresponding C—C—C—O torsion angles are −174.6 (1), −53.2 (2) and −47.3 (2)°]. In the crystal, C—H⋯O interactions link the molecules into [010] chains.